Optimization of tool orientation for improving the cleaning efficiency of offshore jacket-cleaning systems. (July 2021) - Yu, Fujie; Li, Qingzhong; Wang, Yao; Chen, Yuan
Abstract: Marine organisms grow on the jackets of an offshore oil platform, thereby affecting its service life and safety. Therefore, these marine organisms need to be cleaned regularly. Correspondingly, an underwater pipe cleaning system is urgently needed because the conventional manual cleaning is severely limited in underwater missions in terms of duration, depth, and safety. Autonomous underwater intervention robots can provide a longer duration or deeper working depth and allow fast deployment and operation in adverse environments. Hence, an underwater cleaning robot equipped with a six degrees of freedom electric manipulator is developed for marine biofouling stripping tasks. An automatic trajectory planning approach based on the hierarchical task control framework is proposed for efficient and delicate manipulation. In this control approach, we transformed the jet pistol orientation relative to the target surface into an optimization problem on the basis of uncomplicated constraints. Simulations and experimental trials are successively presented to show that the developed robot system provides a solution for a less execution time and robotize pipe-cleaning process.